1972
DOI: 10.1002/kin.550040305
|View full text |Cite
|
Sign up to set email alerts
|

The second limit of hydrogen + carbon monoxide + oxygen mixtures

Abstract: Previous studies by Buckler and Norrish of the second limit of CO and 0 2 mixtures containing small amounts (0.25-10%) of Hz have been used to obtain the velocity constant of the reaction.9 X lo8 and 3.5 X I081iter2mole-zsec-1(M =H2) at500"and 560°C.respectively, have been combined with other estimates over the range 300°-35000K to give ka3 = 3.0 x lOsexp (-3000/RT) for M = Ar; the considerable scatter in the available points does not encourage any great confidence in this expression and may be attributed at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Lloyd [34] suggested that since it was assumed that all the participating reactions had been considered, other reactions aiding the decomposition or the underestimation of surface decomposition effects could affect k 28 . Baldwin et al [37] quoted an unpublished work for a value of k 28 /(k 18 + k 19 ) 1/2 which was obtained at 773 K and was a factor of 24 less than the previous measurement of Baldwin et al [35] at the same temperature. Lloyd [34] reported the values of k 28 obtained by using the recommended expression for (k 18 + k 19 ) along with the measurements of Baldwin et al [35][36][37].…”
Section: Refinement Of Rate Constantsmentioning
confidence: 88%
See 2 more Smart Citations
“…Lloyd [34] suggested that since it was assumed that all the participating reactions had been considered, other reactions aiding the decomposition or the underestimation of surface decomposition effects could affect k 28 . Baldwin et al [37] quoted an unpublished work for a value of k 28 /(k 18 + k 19 ) 1/2 which was obtained at 773 K and was a factor of 24 less than the previous measurement of Baldwin et al [35] at the same temperature. Lloyd [34] reported the values of k 28 obtained by using the recommended expression for (k 18 + k 19 ) along with the measurements of Baldwin et al [35][36][37].…”
Section: Refinement Of Rate Constantsmentioning
confidence: 88%
“…Baldwin et al [37] quoted an unpublished work for a value of k 28 /(k 18 + k 19 ) 1/2 which was obtained at 773 K and was a factor of 24 less than the previous measurement of Baldwin et al [35] at the same temperature. Lloyd [34] reported the values of k 28 obtained by using the recommended expression for (k 18 + k 19 ) along with the measurements of Baldwin et al [35][36][37]. However, when the recently recommended value of Hippler et al [38] for (k 18 + k 19 ) is used, the values of k 28 are a factor of 3 less than those calculated by Lloyd [34].…”
Section: Refinement Of Rate Constantsmentioning
confidence: 88%
See 1 more Smart Citation
“…For conditions corresponding to those of the middle graphs in Figure 5, independent variations of a factor of 3 in k, and k,, Like reaction ( e ) , this reconibination reaction has the largest potential effect at our lowest experimental temperatures, where k b is smallest. Baldwin and co-workers [20] have correlated determinations of k , at 773 and 833°K with directly measured values of k, near room temperature by the conventional Arrhenius expression k , = 3 X lOI4 exp(-12.6 ( k J ) / R T ) cm6/mole*.s for M = Ar, by which the rate coefficient of reaction (p) increases with increasing temperature. The measured rate of COZ dissociation [7], however, implies that above 2550"K, k, decreases with increasing temperature.…”
Section: Infuence Of Other Ratesmentioning
confidence: 99%
“…3 and 4 were not adopted in this study even though the reported rate measurements [3, 4] appear to have smaller estimated uncertainties than the previous measurements [57, 58]. Instead, we again applied a weighted least squares fitting to all experimental data available in the literature for k 24 [3,22, 57,[60][61][62][63][64][65][66][67][68][69][70][71][72][73], to yield a new rate correlation, [57] within 30%, and is about 2~3 times higher than the correlation recommended by Friedrichs 33 et al [3]. Over 500-1300 K where the rate coefficient of (R24) was measured by Friedrichs et al…”
mentioning
confidence: 99%